Sponsor networks and business relations orchestrated by team sports clubs. Issue 4 (11th September 2017) - Wagner, Ulrik; Persson, H. Thomas R.; Overbye, Marie
Abstract : Purpose: The purpose of this paper is to investigate firms' reasons and motives for becoming sponsors and how they benefit from this networking engagement by exploring sponsorship networks associated with two Danish team sport clubs – a Premier League football club and a second-division handball club. Design/methodology/approach: Two online surveys were conducted with firms associated with the networks during the Autumn and Winter of 2013/2014 ( n =116). The questionnaire was theoretically anchored in the existing sponsorship literature, business network research, and social capital theory. Findings: The results show that business logics were the dominating reasons for joining the network. A large proportion of the respondents reported having increased their number of business (32 percent) and social (26 percent) relations with other network members after joining the network. Furthermore, 37 percent of the respondents reported having made business agreements with companies external to the network via network contacts, which supports ideas of bridging social capital. More than half the respondents (59 percent) preferred doing business with network members rather than with non-members. Originality/value: By investigating a local and regional sport club context, the paper adds to our knowledge about sponsorship networks. It emphasizes the potential importance of team sport clubs for the business landscape, thus maintaining that sport clubs fulfill an important role for local communities beyond being mere entertainment industries.